A Multicenter Randomized Control Trial Comparing a Novel Intramedullary Device (InterTAN) Versus Conventional Treatment (Sliding Hip Screw) of Geriatric Hip Fractures. Issue 1 (January 2017) - Sanders, David; Bryant, Dianne; Tieszer, Christina; Lawendy, Abdel-Rahman; MacLeod, Mark; Papp, Steven; Liew, Allan; Viskontas, Darius; Coles, Chad; Gurr, Kevin; Carey, Tim; Gofton, Wade; et al.
Abstract : Objectives: To compare outcomes in elderly patients with intertrochanteric hip fractures treated with either the sliding hip screw (SHS) or InterTAN intramedullary device (IT). Design: Prospective, randomized, multicenter clinical trial. Setting: Five level 1 trauma centers. Patients: Two hundred forty-nine patients 55 years of age or older with AO/OTA 31A1 (43) and OA/OTA 31A2 (206) fractures were prospectively enrolled and followed for 12 months. Intervention: Computer generated randomization to either IT (n = 123) or SHS (n = 126). Main Outcome Measurements: The Functional Independence Measure (FIM) and the Timed Up and Go test (TUG) were used to measure function and motor performance. Secondary outcome measures included femoral shortening, complications, and mortality. Results: Demographics, comorbidities, preinjury FIM scores and TUG scores were similar between groups. Patients (17.2%) who received an IT had limb shortening greater than 2 cm compared with 42.9% who received an SHS ( P < 0.001). To determine the importance of preinjury function and fracture stability, we analyzed the subgroup of patients with the ability to walk 150 m independently preinjury and an OA/OTA 31A-2 fracture (n = 70). In this subgroup, patients treated with SHS had greater shortening and demonstrated poorer FIM and TUG scores compared with patients treated with an IT. Conclusions: Overall, most patients with intertrochanteric femur fractures can expect similar functional results whether treated with an intramedullary or extramedullary device. However, active, functional patients have an improved outcome when the InterTAN is used to treat their unstable intertrochanteric fracture. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.